Analise dos fragmentos florestais para a seleção de áreas prioritárias para conservação no município de Indaiatuba-SP - Carrion, Mayara de Oliveira (Universidade Federal de São Carlos, 2022)
The fragmentation of the Atlantic Forest represents a threat to the biodiversity characteristic of this biome. Landscape Ecology, with the help of Geographic Information Systems and Remote Sensing, uses spatial data to characterize the current conditions of forest fragments through measures that quantify and evaluate the landscape. The present work aimed to analyze the remnants of the municipality of Indaiatuba-SP using the metrics of area, core area and distance to the nearest neighbor, in order to generate a priority indicator for conservation as a way of subsidizing the process of decision-making concerning the planning and adoption of effective conservation measures.The mapping of the fragments was carried out by means of photointerpretation of high resolution orbital images, followed by manual vectorization at a scale of 1:3,000. A total of 887 fragments were mapped, totalizing 3,288.69 ha, which corresponds to 10.56% of the territory studied. The metrics showed that 85.46% of the fragments have up to five ha, in addition to the absence of a core area in 51.41% of the remnants, while 72.83% are within 39 meters of another patch. The analysis of the priority indicator showed only three fragments of very high relevance for conservation, due to their expressive size of area and core area, as well as their proximity to another patch. The results obtained show a high level of fragmentation and low forest cover in most of the municipality's sub-basins, reinforcing the need for the set of remnants to be the target of environmental planning actions.
Analysis of forest fragments for the selection of priority areas for conservation in the municipality of Indaiatuba-SP
Keywords: Geoprocessamento; Ecologia da Paisagem; Fragmentação Florestal; Métricas da Paisagem; Geoprocessing; Landscape Ecology; Forest Fragmentation; Landscape Metrics; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOFISICA